Studying dilemmas of mathematics teaching in Southern Africa - Fraser Gobede; Reidar Mosvold (African Journal of Teacher Education and Development, 2022)
Background: Learners in many countries in sub-Saharan Africa are underperforming in important subjects such as mathematics, and research in these contexts tends to focus on the lack of resources, insufficient teacher knowledge or poor quality in teaching as explanatory factors. This study has taken a different approach.